Nelfinavir and Non-Nucleoside Reverse Transcriptase Inhibitor-Based Salvage Regimes in Heavily Hiv Pretreated Patients - Jean-Guy Baril; Eric A Lefebvre; Richard G Lalonde; Stephen D Shafran; Brian Conway (Canadian Journal of Infectious Diseases)
OBJECTIVE: To assess the efficacy of nelfinavir mesylate (NFV) in combination with delavirdine mesylate(DLV) or efavirenz (EFV) and other antiretroviral agents following virological failure on other protease inhibitor (PI)-based regimens.